Influence of mode of delivery on maternal and fetal outcomes in patients with preterm prelabor rupture of membranes - K. S. Midhuna; Umadevi Vavaldas; Sarada Kandhichetty (MRIMS Journal of Health Sciences)
Background: Diagnosis and proper management are very important to limit various fetal and maternal complications. Preterm prelabor rupture of membranes (PPROM) early diagnosis and intervention decide the further fate of pregnancy. Maternal and fetal outcome in PPROM is very important to decrease maternal and child mortality and for better management and prevention of complications. Objective: The objective is to study the influence of the mode of delivery on maternal and fetal outcomes in patients with PPROM. Materials and Methods: The study was hospital-based prospective-Cohort study done among 204 cases with PPROM. Antepartum and intrapartum events were recorded. Based on the preference of the treating unit and existing hospital protocols, patients undergoing either of the three modes of delivery (cesarean, vaginal, cesarean after failed trial) were observed for maternal and fetal outcomes. Women between 28 and 36 weeks + 6 days period of gestation were divided into three groups. Group A: 10 women (cesarean section), Group B: 174 women (vaginal delivery), and Group C: 20 women (cesarean section after failed trial). Results: Majority women (>60%) in all three groups belonged to the gestational age of 34–36+6. The vaginal delivery group had the least proportion of neonatal complications at 32–33+6 weeks of gestation, and at 34–36+6 weeks of gestation. Sixty percent of women in the failed trial group had complications compared to 50% in the cesarean section group and only 18.9% of the women from the normal vaginal delivery group had complications. This difference was found to be statistically significant. Conclusion: Maternal and neonatal complications were significantly more in the failed trial group followed by the cesarean section group compared to the normal vaginal delivery group.